An Exploration of the Effects of Sexual Assault Victimization among Justice-Involved Youth: Urbanity, Race/Ethnicity, and Sex Differences. Issue 4 (19th May 2022) - Dembo, Richard; Wareham, Jennifer; Schmeidler, James; Wolff, Jessica
ABSTRACT: Childhood sexual assault is a traumatic experience with negative consequences and correlates. Little research has examined the prevalence of self-reported childhood sexual assault among justice-involved youths across urbanity, sex, and race/ethnicity. This study utilized data collected at intake from two juvenile assessment centers (JACs) for 4, 336 adolescents. This exploratory study examined the prevalence of sexual assault victimization and correlates of marijuana use, sexually transmitted infection (STI), number of sexual partners, sexual orientation, and depression across twelve subgroups based on urbanity, sex, and race/ethnicity. Results indicated 7-8% of the sample reported experiencing sexual assault across the urban and rural JAC locations. The prevalence of sexual assault varied significantly across the subgroups, with White, females in both urban and rural locations reporting higher rates, compared to Black or Hispanic males and females. Sexual assault victimization was particularly related to depression, number of sexual partners, and sexual minority orientation. Implications regarding public health concerns are discussed.